Features of business education in context of development of youth entrepreneurship - A. M. Shulzhenko (Омский научный вестник: Серия "Общество. История. Современность")
The development of the youth entrepreneurship sector contributes to an increase in youth employment, the well-being of citizens, the flow of tax revenues to the budget. Despite the obvious positive qualities inherent in young people, a number of negative factors persist, for example, a lack of material resources and experience, lack or insufficient availability of business contacts and knowledge in the field of business. The peculiarity of young people, as a potential business entity, lies in their sensitivity to such a form of support as business education. The article presents the results of a study of the characteristics of business education in the context of the development of youth entrepreneurship. The author suggests the term «business advise», analyzes its impact on youth. The research is based on general scientific methods of classification, generalization, comparison, analysis.